Glucose and Fatty Acid Metabolism of Dairy Cows in a Total Mixed Ration or Pasture-Based System During Lactation - García-Roche, Mercedes; Cañibe, Guillermo; Casal, Alberto; Mattiauda, Diego A.; Ceriani, Mateo; Jasinsky, Alejandra; Cassina, Adriana; Quijano, Celia; Carriquiry, Mariana (Frontiers in Animal Science, 2021)
In this study we explored mechanisms related to glucose and fatty acid metabolism in Holstein-Friesian multiparous dairy cows during lactation under two feeding strategies. From 0 to 180 days postpartum, cows were fed total mixed ration ad libitum (non-grazing group, G0) or grazed Festuca arundinacea or Medicago sativa and were supplemented with 5.4 kg DM/d of an energy-protein concentrate (grazing group, G1). From 180 to 250 days postpartum, all cows grazed Festuca arundinacea and were supplemented with total mixed ration. Plasma samples and liver biopsies were collected at -14, 35, 60, 110, 180 and 250 days in milk for metabolite, hormone, gene expression and western blot analysis. Our results showed increased levels of negative energy balance markers: plasma non-esterified fatty acids, liver triglyceride and plasma β-hydroxybutyrate (P < 0.01), triglyceride and β-hydroxybutyrate concentration were especially elevated for G1 cows. Also, hepatic mRNA expression of gluconeogenic enzymes was upregulated during early lactation (P < 0.05). In particular, methymalonyl-CoA mutase expression was increased for G0 cows (P < 0.05) while pyruvate carboxylase (PC) expression was increased for G1 cows (P < 0.05), suggesting differential gluconeogenic precursors for different feeding strategies. Phosphorylation of AMP-activated protein kinase was increased in early lactation vs. late lactation (P < 0.01) and negatively correlated with PC mRNA levels. The positive association of gluconeogenic genes with proliferator-activated receptor gamma coactivator 1-alpha (PPARGC1A) hepatic expression supported the importance of this transcription factor in glucose metabolism. The peroxisome proliferator-activated receptor alpha (PPARA) mRNA was increased during early lactation (P < 0.05), and was positively associated to PPARGC1A, carnitine palmitoyl-transferase 1 and hydroxymethylglutaryl-CoA synthase 2 (HMGCS2) mRNA expression. Alongside, hepatic mRNA expression of FABP was decreased for G1 vs. G0 cows (P < 0.05), possibly linked to impaired fatty acid transport and related to accumulation of liver triglycerides, evidencing G1 cows fail to adapt to the demands of early lactation. In sum, our results showed that metabolic adaptations related to early lactation negative energy balance can be affected by feeding strategy and might be regulated by the metabolic sensors AMPK, SIRT1 and coordinated by transcription factors PPARGC1A and PPARA.